THE ACCULTURATION OF ISLAM AND KARO CULTURE IN KARO REGENCY IN 19th to 20th CENTURIES - Nursukma Suri; Fitriaty Tambunan; Kus Angelia Tarigan; Rani Anggriani (Universitas Negeri Medan, 2026)
Karo Regency, located in the highlands of North Sumatra, is demographically known as a region with a significant Christian majority. According to data from the Central Statistics Agency of Karo Regency for 2023, Protestant Christians constitute 57.2% of the population, Roman Catholics 19.8%, while Muslims make up only about 21.3% of the total population. This condition has led to the historical narrative of Islam in this region often being marginalized in both national and local historiography. In fact, archaeological and historical evidence indicates a unique process of Islamization in the Karo lands, differing from the pattern of mass conversion on the eastern coast of Sumatra driven by sultanate powers. This research aims to identify, analyze, and reconstruct the Islamic archaeological and historical heritage in Karo Regency, as well as to understand the pattern of acculturation between Islamic teachings and local Karo culture, particularly the Pemena belief system and the merga silima (five clans) customary structure. This qualitative study employs a library research method, critically analyzing various primary sources such as Dutch colonial reports (Joustra, Westenberg, and Neumann), academic manuscripts, recent journal articles (2020-2025), undergraduate theses from various universities, and official documentation from the Regional Office for Cultural Preservation of Zone II, Medan. The research findings identify three main categories of heritage: (1) Ancient tomb sites, such as the Tomb of Nini Tengku in Lingga Village, the Tomb of Tengku Syekh Lau Bahun in Sukanalu, and other tombs of Acehnese scholars, representing the early phase of interaction from the 18th to 19th centuries; (2) Old mosque architecture, such as the Kabanjahe Old Mosque (1902-1904), the Lau Cimba Mosque, and the Nurul Iman Tigabinanga Mosque, which exhibit Acehnese-Malay architectural acculturation with local Karo construction techniques; (3) Intangible cultural manifestations, such as birth, marriage, and death traditions that have been integrated with Islamic values without losing the essence of customs, as well as the emergence of local figures like H. Sulaiman Tarigan as agents of cultural da'wah (Islamic propagation). This research concludes that the existence of Islam in Karo Regency is not a marginal phenomenon or merely a